2013
DOI: 10.1051/0004-6361/201321632
|View full text |Cite
|
Sign up to set email alerts
|

On the structure and dynamics of Ellerman bombs

Abstract: Aims. We study the structure and dynamics of three Ellerman bombs (EBs) observed in an evolving active region. Methods. The active region NOAA 11271 was observed with the Vacuum Tower Telescope at Observatorio del Teide/Tenerife on August 18, 2011. We used the two-dimensional Triple Etalon SOlar Spectrometer (TESOS) to obtain time sequences of the active region and of EBs in Hα at a cadence of 15 s. Simultaneously, we obtained full Stokes profiles with the Tenerife Infrared Polarimeter (TIP II) in the two magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 47 publications
5
37
1
Order By: Relevance
“…However, it is essential that linear Stark broadening, a specific agent for Balmer lines, is included in the line formation computation since without it the Hα wing has less extinction than the continuum. This is demonstrated by the lowest solid curve, which results from only accounting for radiation damping and Van der Waals broadening as done by Bello González et al (2013).…”
Section: Hα Extinction In Ltementioning
confidence: 95%
See 1 more Smart Citation
“…However, it is essential that linear Stark broadening, a specific agent for Balmer lines, is included in the line formation computation since without it the Hα wing has less extinction than the continuum. This is demonstrated by the lowest solid curve, which results from only accounting for radiation damping and Van der Waals broadening as done by Bello González et al (2013).…”
Section: Hα Extinction In Ltementioning
confidence: 95%
“…Kitai (1983), Berlicki et al (2010), Bello González et al (2013) and Berlicki & Heinzel (2014) performed Hα synthesis from best-fit ad-hoc perturbations of a static 1D standard model of the solar atmosphere to reproduce observed Hα wing brightenings. These modeling efforts were summarized in Paper IV together with their failures: nonreproduction of the observed photospheric anchoring of EBs in internetwork lanes (Paper I), non-reproduction of EB brightening in IRIS Si iv and C ii lines (Paper III), and non-reproduction of EB non-visibility in the Na i D and Mg i b lines (Paper IV).…”
Section: Introductionmentioning
confidence: 99%
“…Payne (1993), Berlicki et al (2010), and Bello González et al (2013) found them to lie around the temperature minimum and above it. Some authors suggested that EBs form in the low chromosphere (Matsumoto et al 2008), while others found that they are solely a photospheric phenomena (Watanabe et al 2011;Vissers et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Some studies made a link between EBs and undulating field topologies in emerging flux regions (Pariat et al 2004;Watanabe et al 2008). Bello González et al (2013) found evidence for the existence of opposite magnetic polarities at the sites of three EBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation